2013
DOI: 10.1590/s0100-83582013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência nutricional de cultivares de feijão em competição com plantas daninhas

Abstract: Apesar do ciclo efetivamente rápido do feijoeiro, a habilidade no uso dos nutrientes adicionados por ocasião do plantio e cobertura pode ser prejudicada pela presença de determinadas espécies de plantas daninhas. Objetivou-se com este trabalho avaliar os efeitos da competição entre três cultivares de feijão (IPR Colibri, IPR Eldorado e Pérola) e seis espécies de plantas daninhas (Euphorbia heterophylla, Bidens pilosa, Cenchrus echinatus, Amaranthus spinosus, Commelina benghalensis e Brachiaria plantaginea) no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…This fact was observed for most treatments in which soybean was cultivated with B. pilosa and U. decumbens. Nitrogen and potassium are two elements high extracted by weed (Kabba, Knight, & Rees, 2011;Cury et al, 2013), being a strong competing for these elements.…”
Section: Resultsmentioning
confidence: 99%
“…This fact was observed for most treatments in which soybean was cultivated with B. pilosa and U. decumbens. Nitrogen and potassium are two elements high extracted by weed (Kabba, Knight, & Rees, 2011;Cury et al, 2013), being a strong competing for these elements.…”
Section: Resultsmentioning
confidence: 99%
“…This occurred due to the high density of weeds in the experimental area, an average of 101 and 17 plants m -2 monocots and dicots, respectively, evaluated at 14 DAE, and due to low competitive ability of common bean (PROCOPIO et al, 2004a;CURY et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike what was observed in other studies conducted with rice (BALBINOT JR. et al, 2003a), corn (BEGNA et al, 2001), soybean (BIANCHI et al, 2006) and wheat (LEMERLE et al, 2001), the percentage of soil coverage by common bean plants and the plant height did not estimate consistently the competitive ability of black common bean genotypes. Probably roots characteristics of common bean genotypes influence the competitiveness against weeds, as discussed by Cury et al (2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated that the critical period (4 to 18 days after emergence) for the early-maturing Carioca Precoce cultivar was shorter than the one observed for late-maturing cultivars. Additionally, Cury et al (2013) reported that IPR-Colibri, another early-maturing cultivar, was less tolerant to weed competition than two other common bean cultivars.…”
Section: Key-wordsmentioning
confidence: 99%